SPE Asia Pacific Oil and Gas Conference and Exhibition 1999
DOI: 10.2118/54330-ms
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery Mechanisms of Alkali-Surfactant-Polymer Flooding

Abstract: The experimental study includes phase behavior tests, measurements of interfacial tension (IFT), and coreflood tests. Effects of alkali (sodium carbonate) additives on micro-emulsion phase behavior were determined for a reservoir oil. No emulsion phase was generated for low surfactant concentrations without alkali additives, while an emulsion phase was always formed with alkali. Measurements of the dynamic IFT revealed that when the alkali concentration is as high as 0.7–1.0 wt%, the IFT rapidly increases afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Arihara et al (1999) concluded the oil recovery mechanisms by alkali-surfactant-polymer flooding in sandstone reservoir. They proposed that at alkaline concentration below 1 wt% the wettability reversal mechanism predominates so that the rock wettability is changed from strongly oilwet to the lesser oil-wet condition.…”
Section: Formation Of O/w Emulsion Emulsification and Entrainmentmentioning
confidence: 97%
“…Arihara et al (1999) concluded the oil recovery mechanisms by alkali-surfactant-polymer flooding in sandstone reservoir. They proposed that at alkaline concentration below 1 wt% the wettability reversal mechanism predominates so that the rock wettability is changed from strongly oilwet to the lesser oil-wet condition.…”
Section: Formation Of O/w Emulsion Emulsification and Entrainmentmentioning
confidence: 97%
“…By altering the wet ability to the water-wet condition and reducing the interfacial tension to ultra-low values [4], it is possible to enhance oil recovery and provide a solution to oil retention problem. An injected fluid is required to be injected into the matrix of a fractured formation for EOR rather than into the fractures.…”
Section: Theoretical Discussion For Eormentioning
confidence: 99%
“…To meet the requirements of crude oil supply, more and more efforts have been placed on not onlyexploringnew oil reservoirs, but also further improving of oil recovery from the mature reservoirs [2,3]. The improvement of oil production from mature oil fields is an important strategy from both economic and technical points of view [1,2,4]. According to the oil recovery history [5,6], there are three stages of oil extraction, which are primary, secondary, and tertiary technologies [7].…”
Section: Introductionmentioning
confidence: 99%
“…Field applications of alkaline floods alone usually result in poor oil recovery due to the alkaline loss caused by the chemical reactions with the reservoir rocks, low acid number of the crude oil, and adverse mobility ratio 10 . The major EOR mechanisms of an ASP flood are briefly described as follows.…”
Section: Introductionmentioning
confidence: 99%